FINANCIAL STABILITY IN THE MANAGEMENT SYSTEM OF ENTERPRISES: SYSTEM ANALYSIS AND FORMALIZATION OF ASSESSMENTS IN THE CONDITIONS OF SUSTAINABLE DEVELOPMENT - Зеновій-Михайло Задорожний; Володимир Муравський; Світлана Жукевич; Надія Хома; Ірина Данилюк; Роман Башуцький (Фінансово-кредитна діяльність: проблеми теорії та практики)
The idea of sustainable development entails the modernization of the financial mechanism and the development of financial activity models in the context of ensuring their stability at various levels of economic management. Financial stability refers to the state of financial resources where assets and liabilities are balanced in a fluctuating internal and external environment, maintaining financial solvency and appealing to investors, all while operating within a manageable risk threshold. The analysis of such indicators allows for assessing the enterprise's readiness to meet its debts, financial independence, and efficient management of own and borrowed funds. The aim of this article is to explore theoretical and methodological approaches and methods of systemic analysis of the financial stability of enterprises under conditions of sustainable development. The theoretical foundations and methodological approaches to systemic analysis of financial stability were studied. The financial stability analysis of enterprises was conducted using a methodology for calculating the coverage of assets by their financing sources. The proposed financial stability calculation algorithm utilizes a balance model of financial equilibrium and involves computing a three-component indicator to determine the optimal coverage levels for financing sources using both absolute and relative metrics. This method enables the identification of weak areas within a company, which can serve as potential reserves for enhancing its financial standing. Analytical indicators that form part of the systemic financial stability analysis include the financial independence ratio (autonomy), the financial dependency ratio (equity multiplier), the loan capital concentration ratio, the financial risk ratio, the financial stability ratio, the long-term debt ratio, and the equity mobility ratio. The calculation of the proposed analytical indicators for assessing financial stability across enterprises of various organizational and legal forms and business sizes demonstrated the universality and broad applicability of this systemic analysis methodology.